Maintenance of sarcomeric integrity in adult muscle cells crucially depends on Z-disc anchored titin - Swist, Sandra (Nat Commun, 2020)
The giant protein titin is thought to be required for sarcomeric integrity in mature myocytes, but direct evidence for this hypothesis is limited. Here, we describe a mouse model in which Z-disc-anchored TTN is depleted in adult skeletal muscles. Inactivation of TTN causes sarcomere disassembly and Z-disc deformations, force impairment, myocyte de-stiffening, upregulation of TTN-binding mechanosensitive proteins and activation of protein quality-control pathways, concomitant with preferential loss of thick-filament proteins. Interestingly, expression of the myosin-bound Cronos-isoform of TTN, generated from an alternative promoter not affected by the targeting strategy, does not prevent deterioration of sarcomere formation and maintenance. Finally, we demonstrate that loss of Z-disc-anchored TTN recapitulates muscle remodeling in critical illness ‘myosinopathy’ patients, characterized by TTN-depletion and loss of thick filaments. We conclude that full-length TTN is required to integrate Z-disc and A-band proteins into the mature sarcomere, a function that is lost when TTN expression is pathologically lowered.